2014
DOI: 10.1016/j.tcb.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Damage control: cellular mechanisms of plasma membrane repair

Abstract: Summary When wounded, eukaryotic cells reseal in a few seconds. Ca2+ influx induces exocytosis of lysosomes, a process previously thought to promote repair by “patching” wounds. New evidence suggests that resealing involves direct wound removal. Exocytosis of lysosomal acid sphingomyelinase triggers endocytosis of lesions, followed by intracellular degradation. Characterization of injury-induced endosomes revealed a role for caveolae, sphingolipid-enriched plasma membrane invaginations that internalize toxin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
272
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(286 citation statements)
references
References 74 publications
8
272
2
4
Order By: Relevance
“…Live-cell imaging showed that complement exposure increased [Ca 2+ ] i and stimulated lysosome exocytosis. Lysosomal hydrolases and lipids released during exocytosis have been proposed to remodel the cell surface and limit membrane damage caused by pore-forming toxins (29). We show here that inactivating lysosomes causes sustained [Ca 2+ ] i elevation and mitochondrial fragmentation, indicating that lysosome exocytosis is a key mechanism for curtailing the downstream consequences of complement attack in the RPE.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Live-cell imaging showed that complement exposure increased [Ca 2+ ] i and stimulated lysosome exocytosis. Lysosomal hydrolases and lipids released during exocytosis have been proposed to remodel the cell surface and limit membrane damage caused by pore-forming toxins (29). We show here that inactivating lysosomes causes sustained [Ca 2+ ] i elevation and mitochondrial fragmentation, indicating that lysosome exocytosis is a key mechanism for curtailing the downstream consequences of complement attack in the RPE.…”
Section: Discussionmentioning
confidence: 60%
“…In many cell types, elevated [Ca 2+ ] i has been shown to trigger fusion of lysosomes with the plasma membrane (25,28). Lysosome exocytosis, mediated by the lysosomal calcium sensor synaptotagmin 7 (Syt7), is vital for preserving membrane integrity after exposure to pore-forming toxins (29). We used live-cell imaging by total internal reflection fluorescence (TIRF) microscopy and complementary biochemical assays to determine whether sublytic MACs stimulate lysosome exocytosis in the RPE.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to improving our understanding of endothelial cell responses to membrane rupture, such as mitochondrial fission, tilted microindentation provides a highly versatile tool for studying membrane repair. Indeed, membrane repair processes are expected to differ depending on the size of the wound created in the membrane (55), which can be tuned by applying a controlled force with an indenter of controlled size. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that exocytosis of lysosomes contributes to the resealing of plasma membrane (Miyake and McNeil, 1995;Reddy et al, 2001;Chakrabarti et al, 2003;Andrews et al, 2014). By contrast, rapsyn has also been shown to interact with cytoskeletal proteins (Dobbins et al, 2008).…”
Section: Rapsyn Controls Lysosomal Exocytosismentioning
confidence: 99%
“…Increasing evidence suggests that lysosomal positioning plays an important role in coordinating cellular responses during nutrient starvation (Korolchuk et al, 2011). It has also been shown that lysosomal exocytosis plays an essential role in the resealing of the plasma membrane after damage (Miyake and McNeil, 1995;Reddy et al, 2001;Chakrabarti et al, 2003;Andrews et al, 2014). Here, we sought to examine whether rapsyn can be a key regulatory component of the dynamic state of lysosomes, notably lysosomal exocytosis.…”
Section: Introductionmentioning
confidence: 99%